Ketimpangan Luas Lahan Dan Ketersediaan Pangan Pokok Di Kabupaten Sumba Timur - Rinto Tamu Ama; Elfis Umbu Katongu Retang; Junaedin Wadu (Sigmagri, 2022)
This research aims to find out the magnitude of the level of widespread inequality of planting and widespread inequality of basic food harvest of production between sub-districts in East Sumba Regency. The data in this study used secondary data of time series during 2017 - 2020 found in 22 sub-districts in East Sumba Regency.The analysis methods used are the Williamson Index and the Length of Food Availability. The results of the analysis showed high inequality in planting area and area of staple food harvest between sub-districts in East Sumba Regency. Williamson's inequality index for planting area is 0.59 and harvest area is 0.58. This high inequality occurs due to the widespread distribution of planting and uneven harvest area and is also caused by the number of residents between sub-districts. The average availability of rice equivalent staple food at the level of East Sumba Regency reached the adequacy of basic food for 2,830 days. This means that East Sumba Regency has been able to meet food adequacy for 365 days.in East Sumba Regency, there are 3 sub-districts that have not had enough food availability for 365 days, namely Waingapu City only enough for 13 days, Kanatang 273 days and Haharu 347 days.